Revealing the prognostic and clinicopathological significance of systemic immune-inflammation index in patients with different stage prostate cancer: A systematic review and meta-analysis - Qi, Wenqiang; Zhou, Yongheng; Liu, Zhifeng; Wang, Jian; Lv, Guangda; Zhong, Minglei; Wang, Wenfu; Li, Rongyang; Chen, Shouzhen; Shi, Benkang; Zhu, Yaofeng (Frontiers in Medicine, 2022)
Background: A novel inflammatory marker called the systemic immune-inflammation index (SII) was applied to predict the prognosis of different cancers. However, the role of SII in prostate cancer (PCa) remains unclear. This systematic review aims to explore the prognostic role of SII in different-stage PCa. Methods: We comprehensively searched three public databases: PubMed, EMBASE, and the Cochrane Library. The hazard ratios (HRs) and odds ratios (ORs) with 95% confidence intervals (CIs) were extracted to evaluate the association between SII and the prognosis and clinicopathological characteristics in different stage PCa patients. Results: Ten studies and 7986 patients were enrolled in our meta-analysis, 1442 patients were diagnosed with metastatic castration resistant prostate cancer (mCRPC), and 6544 patients were diagnosed with non-metastatic prostate cancer (nmPCa). According to the pooled results, we found that a high SII was associated with worse overall survival (OS) in mCRPC patients (HR = 1.94, 95% CI 1.26–3.01, p=0.003), and a high SII was associated with biochemical recurrence-free survival (BFS) in nmPCa patients (HR = 1.85, 95% CI 1.06–3.24, p=0.031). But there was no significant association observed between SII and progression-free survival (PFS) in mCRPC patients (HR = 1.90, 95% CI 0.87–4.14, p=0.107). And we found that the high SII was associated with advanced tumor stage of PCa (OR: 2.19, 95% CI:1.11-4.33, p=0.024), presence of lymph node involvement (OR: 2.72, 95% CI:1.96-3.76, p <0.001) and Gleason score (OR: 1.27, 95% CI:1.13-1.44, p <0.001). Conclusion: High SII was associated with bad OS in mCRPC patients, and associated with bad BFS and some adverse pathological features in nmPCa patients. We think SII can be a prognostic predictor for PCa patients. The application of SII will advance the diagnosis and treatment of different-stage prostate cancer.